Serum potassium responses to nebulized salbutamol administered during an acute asthmatic attack. Issue 1 (March 1989) - DaCruz, D; Holburn, C
Abstract : A prospective study of 20 patients presenting to an accident and emergency department with an exacerbation of pre-existing reversible airways disease was undertaken in order to determine whether such patients incurred any changes in their serum potassium following administration of 5 mg of nebulized salbutamol. Electrolytes were estimated before and 30 min after administration of nebulized salbutamol. No other drug was administered during this period. Results indicate that nebulized salbutamol can cause a significant hypokalaemic response in such situations. Eight out of the 20 patients studied demonstrated falls in serum potassium of more than 0.3 mmol/l. Most of the falls in serum potassium occurred in patients with low pre-treatment PCO2 values; a group of patients with less severe respiratory distress. This preliminary study indicates that a further study aimed at elucidating the clinical significance of nebulized salbutamol-induced hypokalaemia is required.